Peran Kolaboratif Organisasi Masyarakat Sipil mengintegrasikan Nilai-Nilai Hak Asasi Manusia dalam Tata Kelola Bisnis Perkebunan Sawit di Sumatera Utara - Majda El Muhtaj; Fazli Rachman (Jurnal HAM, 2022)
This study aims to explore the collaborative effort by the Civil Society Organization (CSO) and its significance to encourage corporations in terms of compliance and implementation of the United Nations Guiding Principles on Business and Human Rights (UNGP), particularly in palm oil plantations in North Sumatra. Integration of human rights values into conducting business activities is mandated by UNGP. Indeed, each of the principal actors of UNGP has a governance system to govern their powers and influences and a so-called polycentric governance system. Therefore, a collaboration strategy for strengthening synergy to implement UNGP is needed. This research is conducted by qualitative analysis method with an exploratory design study by collecting data through interviews and various secondary references related to UNGP and its commentaries and reports on this relevant study. The result indicates that PKPA’s programs enhance the capacity building of the primary stakeholder including people who are potentially affected by the company’s activities. This is the strategic partnership to incorporate UNGP into palm oil plantation business activities. This research recommends that the PKPA’s programs, especially REBOUND can be able to be developed by creating new participative modelsto strengthen the implementation of UNGP, mainly human rights due diligence mechanism and access to effective remedies affected by corporations.